The Islamic Republic of Iran : Report on Public Financial Management, Procurement, and Expenditure Systems in Iran - World Bank (Washington, DC, 2012)
This review aims to describe, and to the extent possible, analyze public expenditure management systems in Iran, including those involved in budget formulation and execution, financial management, procurement, and oversight (but not the management of the civil service). As such, it contains elements of a Public Expenditure Review, a Country Financial Accountability Assessment, and a Country Procurement Assessment Report. The report stops short of recommending additional or different reforms or action programs, pending further collaborative work within the agreed multiyear program. This report presents a baseline of understanding, bolstered by selected analytical and comparative diagnoses, on which the Bank can begin to tailor its work with Iran in the area of public financial management. The main chapters of the report thus summarize the size, structure, and functioning of the Iranian budget system, covering public spending performance, resource allocation, and expenditure execution. The final chapter contains a framework for assessing public financial risk in Iran, which summarizes the salient risk characteristics of the Iranian system and efforts to attenuate them. This framework could provide an agenda for future discussions on follow-up work.